The impact of automation on pharmacy staff experience of workplace stressors. (6th August 2012) - James, K. Lynette; Barlow, Dave; Bithell, Anne; Hiom, Sarah; Lord, Sue; Oakley, Pat; Pollard, Mike; Roberts, Dave; Way, Cheryl; Whittlesea, Cate
Abstract Objective Determine the effect of installing an original pack automated dispensing system (ADS) on staff experience of occupational stressors. Methods Pharmacy staff in a National Health Service hospital in Wales, UK, were administered an anonymous occupational stressor questionnaire pre‐ (n = 45) and post‐automation (n = 32). Survey responses pre‐ and post‐automation were compared using Mann–Whitney U test. Statistical significance was P ≤ 0.05. Four focus groups were conducted (two groups of accredited checking technicians (ACTs) (group 1: n = 4; group 2: n = 6), one group of pharmacists (n = 17), and one group of technicians (n = 4) post‐automation to explore staff experiences of occupational stressors. Focus group transcripts were analysed according to framework analysis. Key findings Survey response rate pre‐automation was 78% (n = 35) and 49% (n = 16) post‐automation. Automation had a positive impact on staff experience of stress (P = 0.023), illogical workload allocation (P = 0.004) and work–life balance (P = 0.05). All focus‐group participants reported that automation had created a spacious working environment. Pharmacists and ACTs reported that automation had enabled the expansion of their roles. Technicians felt like 'production‐line workers.' Robot malfunction was a source of stress. Conclusion The findings suggest that automation had a positive impact on staff experience of stressors, improving working conditions and workload. Technicians reported that ADS devalued their skills. When installing ADS, pharmacy managers must consider the impact of automation on staff. Strategies to reduce stressors associated with automation include rotating staff activities and role expansions.